Using Cultural Historical Activity Theory to understand how emerging technologies can mediate teaching and learning in a mathematics classroom: a review of literature - Marjorie Sarah Kabuye Batiibwe (The Asia-Pacific Society for Computers in Education (APSCE), 2019)
Abstract The purpose of this paper was to review literature on the Cultural Historical Activity Theory (CHAT) and how it has been used to understand the mediation between emerging technologies and teaching and learning in a mathematics classroom. Specifically, it aimed at understanding the genesis of CHAT and further analyzing the studies that have employed CHAT as an analytical framework for teaching and learning in a mathematics classroom context. Two major concerns arise out of this review. Firstly, CHAT has been synonymously used with Activity Theory, leaving one wondering what actually the difference between the two in terms of researchers' conceptualization is. Secondly, although CHAT has been widely utilized in education research, scholarly articles that have employed it as their theoretical or analytical frameworks in a mathematics classroom context are still too few and yet still, the few that have utilized it have not exploited its maximum potential. The implications for this review for teachers in Uganda are active student engagement and creation of collaboration spaces for dialogue and interaction in the teaching and learning process.